2007
DOI: 10.1007/s10573-007-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

Ignition, combustion, and agglomeration of encapsulated aluminum particles in a composite solid propellant. II. Experimental studies of agglomeration

Abstract: The combustion characteristics of propellants containing AP, HMX, an energetic binder, and aluminum particles with various polymer coatings are studied at pressures of 0.15 and 4.6 MPa. It is found that the coatings influence the burning rate, the particle size distribution of condensed combustion products, and the completeness of aluminum combustion. It is shown that the agglomeration can be reduced by using aluminum with fluorine-containing coatings. The application of some coatings results in a reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The benefits of including fluorinated oxidizers in systems involving aluminum combustion were discussed previously [12]. In many recent studies, fluoropolymers were combined with aluminum as oxidizers, e. g., [13][14][15][16] or additives to oxidizers or coatings [17,18]. However, the initiation of such aluminumfluoropolymer systems is significantly more difficult than that of a nanothermites.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of including fluorinated oxidizers in systems involving aluminum combustion were discussed previously [12]. In many recent studies, fluoropolymers were combined with aluminum as oxidizers, e. g., [13][14][15][16] or additives to oxidizers or coatings [17,18]. However, the initiation of such aluminumfluoropolymer systems is significantly more difficult than that of a nanothermites.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, experiments with iron-coated Al particles have shown that such particles ignite at a surface temperature 1600-1700 K and hence could also be used for propulsion applications [79]. Finally, it is worthwhile to investigate nonmetal coatings, such as fluorinecontaining polymers [80][81][82] and complex fluorides [83], as methods to facilitate ignition of Al particles in CO 2 atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…3). The confidence interval Δ is estimated by means of a reproducibility test [3] for a confidence probability of 68%. As is evident in Fig.…”
Section: Morphology Size and Number Of Sampled Particlesmentioning
confidence: 99%